Comprehensive Assessment of Health Needs of Young Minority Males Attending a Family Planning Clinic. (May 2017) - Pastuszak, Alexander W.; Wenker, Evan P.; Smith, Peggy B.; Abacan, Allyssa; Lamb, Dolores J.; Lipshultz, Larry I.; Buzi, Ruth
The objective of this study was to assess the overall health, including sexual and reproductive health (SRH) knowledge and needs, sexual behaviors, and testicular health practices among young minority males. Anonymous questionnaires were administered to 18- to 25-year-old males receiving services at health clinics in a large southwestern U.S. city. The survey was completed by 258 males with a mean age of 20.8 years. Most young males (67.1%) identified as African American, and 32.9% as Hispanic. Results suggest study participants lack SRH knowledge related to pregnancy and condom effectiveness, and engage in risky sexual behavior including not using birth control at their last sexual encounter. Although 21.6% of participants had a sexually transmitted infection (STI) in the past year, approximately 80% perceived their STI/HIV risk as very low or low. Respondents had low engagement and lack of knowledge of testicular health practices. The majority of respondents (71.1%) reported having been in a physical fight one or more times and 18.1% reported being victims of intimate partner violence. These data support a need for comprehensive health services for minority young males.